Peran Kebijakan Ekonomi Pemerintah Dalam Mendorong Pertumbuhan Ekonomi Nasional Indonesia - Wira Yudha Alam; Nadia Alkhalifi Dwi Ramadhani; Muhles; Nur Irvia Dhea Agustin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Economic growth is one of the main indicators in assessing the success of a country's development. Stable economic growth reflects an increase in production, consumption, investment, and public welfare activities. In the Indonesian context, the government has a very important role in regulating and directing the national economy through various economic policies. The government's economic policy basically aims to maintain economic stability, encourage economic growth, create jobs, and improve the welfare of the community. This research aims to analyse the role of government economic policy towards Indonesia's economic growth. The research method used is qualitative descriptive with a literature study approach. The data used is secondary data obtained from books, scientific journals, official reports of the Central Statistics Agency (BPS), Bank Indonesia, Ministry of Finance, and other relevant sources. Research results show that the government's economic policy has a significant role in driving Indonesia's economic growth. Fiscal policy plays a role through government spending, subsidies, tax incentives, and infrastructure development. Monetary policy plays a role in maintaining the stability of inflation, interest rates, and the rupiah exchange rate. Meanwhile, structural reform plays a role in increasing productivity, investment, economic competitiveness, and transformation of the national economic sector. Thus, Indonesia's economic growth cannot be separated from the effectiveness and synergy of government economic policies that are implemented sustainably.